Women's Rights in Government of a Democratic Society - Inoyatkhon Madimarovna Arzimatova (Genius Publishing Group, 2021)
The article discusses issues such as increasing women's employment, improving material security, and ensuring that states develop their own strategies in this regard.
Keywords: Democracy; Gender; Political Activism; National Law